UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS IV.d SD N 09 PASAMAN - driva susila (STKIP Pesisir Selatan, 2017)
AbstractBased on the results of student learning Class 09 SD IV.d Pasaman in science sub Describe the life cycle of some animals in the neighborhood, such as cockroaches, mosquitoes, butterflies, cats found that results for students in science subjects sub Describe the life cycle of some animals in the neighborhood, such as cockroaches, mosquitoes, butterflies, cats are still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in science sub Describe the life cycle of some animals in the neighborhood, such as cockroaches, mosquitoes, butterflies, cats through Jigsaw Cooperative Learning Model in Class IV.d SD 09 Pasaman West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 33 students Grades IV.d SD 09 Pasaman. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Model Cooperative Learning Jigsaw can improve student learning outcomes in science sub Describe the life cycle of some animals in the neighborhood, such as cockroaches, mosquitoes, butterflies, cats in SD N 09 Pasaman. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 46.42 (less) increased to 84.33 (good) with an increase of 37.91%.Keywords: Learning Outcomes, IPA, Model Cooperative Learning Jigsaw